Feedbacks in a mixed mycorrhizal rainforest in Sri Lanka are more stabilizing in the field than in the shadehouse - Akshay Surendra; H. K. Mahesha Lakmali; H. A. Shashikala Madhubhani; H. M. S. Chaturanga Jayathilaka; K. M. Upul Shantha; Mark S. Ashton; Sisira Ediriweera; Liza S. Comita (Plant and Soil, 2026)

Dual-nutrient stress tolerance in wheat is regulated by nitrogen and phosphorus uptake, assimilation, reutilization, and differential expression of candidate genes - Renu Pandey; Sandeep Sharma; Ankita Mishra; Akshay Sureshrao Sakhare; Surendra Kumar Meena; Krishnapriya Vengavasi (Plant and Soil, 2025)

Consequences of Local Conspecific Density Effects for Plant Diversity and Community Dynamics - Joseph A. LaManna; Florian Hartig; Jonathan A. Myers; Robert P. Freckleton; Matteo Detto; Akshay Surendra; Cole J. Doolittle; Bénédicte Bachelot; Robert Bagchi; Liza S. Comita; David M. DeFilippis; Nohemi Huanca‐Nunez; et al. (Ecology Letters, 2024)
Conspecific density dependence (CDD) in plant populations is widespread, most likely caused by local‐scale biotic interactions, and has potentially important implications for biodiversity, community composition, and ecosystem processes. However, progress in this important area of ecology has been hindered by differing viewpoints on CDD across subfields in ecology, lack of synthesis across CDD‐related frameworks, and misunderstandings about how empirical measurements of local CDD fit within the context of broader ecological theories on community assembly and diversity maintenance. Here, we propose a conceptual synthesis of local‐scale CDD and its causes, including species‐specific antagonistic and mutualistic interactions. First, we compare and clarify different uses of CDD and related concepts across subfields within ecology. We suggest the use of local stabilizing/destabilizing CDD to refer to the scenario where local conspecific density effects are more negative/positive than heterospecific effects. Second, we discuss different mechanisms for local stabilizing and destabilizing CDD, how those mechanisms are interrelated, and how they cut across several fields of study within ecology. Third, we place local stabilizing/destabilizing CDD within the context of broader ecological theories and discuss implications and challenges related to scaling up the effects of local CDD on populations, communities, and metacommunities. The ultimate goal of this synthesis is to provide a conceptual roadmap for researchers studying local CDD and its implications for population and community dynamics.